4x+10=11x+3

Simple and best practice solution for 4x+10=11x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+10=11x+3 equation:


Simplifying
4x + 10 = 11x + 3

Reorder the terms:
10 + 4x = 11x + 3

Reorder the terms:
10 + 4x = 3 + 11x

Solving
10 + 4x = 3 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
10 + 4x + -11x = 3 + 11x + -11x

Combine like terms: 4x + -11x = -7x
10 + -7x = 3 + 11x + -11x

Combine like terms: 11x + -11x = 0
10 + -7x = 3 + 0
10 + -7x = 3

Add '-10' to each side of the equation.
10 + -10 + -7x = 3 + -10

Combine like terms: 10 + -10 = 0
0 + -7x = 3 + -10
-7x = 3 + -10

Combine like terms: 3 + -10 = -7
-7x = -7

Divide each side by '-7'.
x = 1

Simplifying
x = 1

See similar equations:

| -9x-7y=-63 | | 2(2x-4)-(x+4)= | | -2a^2+9a+7=0 | | (x+1)(x-9)=39 | | 2(2x^2-3x-20)=0 | | 12+9y=15 | | 5s^2-10s=23 | | (a^2-4a+6)+(-3a^2+13a+1)=0 | | 625000000=(125000+x)+x | | 22120/18 | | 0=-16t+8t+48 | | -3(7n+2)= | | -5x+7y=21 | | 336=(x+4)+x | | d=jqx | | x^2+y^2-4x-6y+11=0 | | (-7x+1)-(-6x-5)=1 | | 8cos(8x)=0 | | -(7x+1)-(-6y-5)=1 | | 3x+27y=54 | | 3(x^2+20)=18 | | 3+15x-2=8x+105-6x | | 5x^2+17x+5=0 | | x/81=38 | | 5y+4y+7y-8= | | x/56=90 | | 4x=18/2x | | 2x^2+11+15=0 | | x/8=-28 | | 8x^2-82=-10 | | 4(-x+5)=11[5(4x-2)] | | 5x+45=122 |

Equations solver categories